Atlantic salmon in regulated rivers: Understanding river management through the ecosystem services lens. Issue 2 (9th November 2021) - Watz, Johan; Aldvén, David; Andreasson, Patrik; Aziz, Khadija; Blixt, Marco; Calles, Olle; Lund Bjørnås, Kristine; Olsson, Ivan; Österling, Martin; Stålhammar, Sanna; Tielman, Johan; Piccolo, John J.
Abstract: Known as the "king of fishes, " the Atlantic salmon ( Salmo salar, Salmonidae) is an iconic freshwater species whose contribution to human well‐being has long been recognized, as have widespread declines in its abundance, partly due to river regulation. To understand how salmon conservation has been addressed within the ecosystem services (ES) framework, we synthesized the peer‐reviewed literature on ES provided by salmon in regulated rivers. We developed a search string to capture allusions to provisioning, regulating, supporting and cultural ES and assessed the results to identify knowledge gaps. The effects of hydropower on fisheries catches and on modelled populations were shown in several publications. Overall, few studies focused explicitly on ES from salmon and hydropower; this is surprising given the considerable body of literature on salmon in regulated rivers. Wild salmon as a food source and other provisioning services are less important today than historically. Because predators such as salmon are important for facilitating biodiversity by cycling nutrients and controlling food webs, there is a scope of work for future assessments of these regulating and supporting services. Few papers explicitly addressed cultural ES, despite the salmon's longstanding iconic status; this is a knowledge gap for future ES assessments in relation to hydropower. The influence of ES assessments for policy makers is growing through the Intergovernmental Panel for Biodiversity and Ecosystem Services (IPBES) and the post‐2020 biodiversity strategy. Explicitly addressing ES poses an opportunity for river managers to raise awareness of aquatic conservation efforts and well‐informed decision‐making for sustaining ES.